Genetic diversity of donkey populations from the putative centers of domestication. (16th December 2014) - Rosenbom, S.; Costa, V.; Al‐Araimi, N.; Kefena, E.; Abdel‐Moneim, A. S.; Abdalla, M. A.; Bakhiet, A.; Beja‐Pereira, A.
Summary Donkey domestication drastically changed ancient transport systems in Africa and Asia, enabling overland circulation of people and goods and influencing the organization of early cities and pastoral societies. Genetic studies based on mtDNA have pointed to the African wild ass as the most probable ancestor of the domestic donkey, but questions regarding its center of origin remain unanswered. Endeavoring to pinpoint the geographical origin of domestic donkey, we assessed levels and patterns of genetic diversity at 15 microsatellite loci from eight populations, representing its three hypothesized centers of origin: northeast Africa, the Near East and the Arabian Peninsula. Additionally, we compared the donkey genotypes with those from their wild relative, the African wild ass (Equus africanus somaliensis) to visualize patterns of differentiation among wild and domestic individuals. Obtained results revealed limited variation in levels of unbiased expected heterozygosity across populations in studied geographic regions (ranging from 0.637 in northeast Africa to 0.679 in the Near East). Both allelic richness (Ar) and private allelic richness presented considerably higher values in northeast Africa and in the Arabian Peninsula. By looking at variation at the country level, for each region, we were able to identify Sudan and Yemen as the countries possessing higher allelic richness and, cumulatively, Yemen also presented higher values for private allelic richness. Our results support previously proposed northeast Africa as a putative center of origin, but the high levels of unique diversity in Yemen opens the possibility of considering this region as yet another center of origin for this species.